Bronchoscopically-visible massive central airway cancer cavitation is associated with metastatic disease, lack of actionable mutations and poor prognosis: a case series - Daniele Magnini; Emilio Bria; Alessandra Cancellieri; Vanina Livi; Fausto Leoncini; Marco Ferrari; Teresa Bruni; Daniela Paioli; Rocco Trisolini (Monaldi Archives for Chest Disease, 2023)
Cavitating lung tumors occur in approximately 10-15% of the patients, are more commonly associated with squamous histology, and are typically located in the lung parenchyma. Herein we describe an exceedingly rare series of 5 patients, 4 of whom treatment-naïve, whose tumor caused the disruption of the normal airway anatomy at the level of lobar or segmental bronchi, leading to the formation of an endoscopically-visible cavity which ended up in the lung parenchyma or even into the pleural space. Sex (3 males, 2 females), smoking habit (2 never smokers, 2 former smokers, 1 current smoker), and histology (3 adenocarcinoma, 2 squamous cell carcinoma) were heterogeneous, but the 4 patients treatment-naïve presented with metastatic disease, poor ECOG performance status, similar clinical complaints of long duration, and lack of actionable mutations. The only patient who exhibited a meaningful response to treatment had the lowest symptoms’ duration, the smallest size of the cavitated mass, and the best performance status at the time of diagnosis. This series provides the first comprehensive description of a rare presentation of lung cancer characterized by similar clinical complaints, delayed diagnosis and poor prognosis.